Early risk factors for death in neonates with persistent pulmonary hypertension of the newborn treated with inhaled nitric oxide - Qian, Ai-Min; Zhu, Wen; Yang, Yang; Lu, Ke-Yu; Wang, Jia-Li; Chen, Xu; Guo, Chu-Chu; Lu, Ya-Dong; Rong, Hui; Chneg, Rui (Zhongguo dang dai er ke za zhi, 2022)
To evaluate the early risk factors for death in neonates with persistent pulmonary hypertension of the newborn (PPHN) treated with inhaled nitric oxide (iNO). A retrospective analysis was performed on 105 infants with PPHN (gestational age ≥34 weeks and age <7 days on admission) who received iNO treatment in the Department of Neonatology, Children's Hospital of Nanjing Medical University, from July 2017 to March 2021. Related general information and clinical data were collected. According to the clinical outcome at discharge, the infants were divided into a survival group with 79 infants and a death group with 26 infants. Univariate and multivariate Cox regression analyses were used to evaluate the risk factors for death in infants with PPHN treated with iNO. The receiver operating characteristic (ROC) curve was used to calculate the cut-off values of the factors in predicting the death risk. A total of 105 infants with PPHN treated with iNO were included, among whom 26 died (26/105, 24.8%). The multivariate